Nursing Students' Opinions on the Individual and Professional Acquisitions Achieved through Hidden Curriculum: A Cross-Sectional Study. - BAYRAKTAR DEDEMOĞLU, Şefika; YACAN KÖK, Ayşe; KOL, Emine (Journal of Nursology, 2025)
Objective: This study was conducted to determine the opinions of nursing students on the individual and professional acquisitions achieved through hidden curriculum. Methods: A descriptive cross-sectional survey design was used to collect quantitative data in 2019-2020 academic year. The sample consisted of 395 nursing students from the Faculty of Nursing at Akdeniz University. Data were collected using a Personal Information Form and the Hidden Curriculum Evaluation Scale in Nursing Education. Results: Participants had a mean total Hidden Curriculum Evaluation Scale in Nursing Education score of 158.94±22.38 (min:91 max:206). Participants gave the highest scores to the items "The staff at the school are helpful and friendly", "The instructor's approaches increase my desire to like the profession", and "I have learned to respect other people's values, beliefs and opinions throughout my education". However, they gave the lowest scores to the items, "The materials used in the courses are associated with a certain point of view", "Nursing is a valuable and valid profession in society" and "Instructors treat students they feel close to with more understanding and kindness". Conclusion: According to the results research, students' opinions regarding student-teacher-school interaction, individual and professional acquisitions are positive. Based on this result, it is possible to say that students hidden acquire humanitarian and professional values during the nursing education process.